PERLINDUNGAN WARGANEGARA INDONESIA (WNI) DARI KEJAHATAN TRANSNASONAL - Yanto, Suci Putriana; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Transnational crimes are becoming an increasingly serious threat in the era of globalization, significantly impacting the security and well-being of Indonesian citizens (WNI) both domestically and abroad. Crimes such as human trafficking, drug smuggling, and online fraud undermine social stability and violate human rights. The Indonesian government has taken preventive and repressive measures through national regulations, ratification of international conventions, and strengthening the diplomatic role of the Indonesian Embassies (KBRI) and Consulates General (KJRI). However, challenges such as limited resources and the continuously evolving modus operandi of these crimes reveal existing gaps in the protection of WNI. This research employs a qualitative method with a descriptive approach, utilizing primary data from observations and interviews, as well as secondary data from official documents. A case study of human trafficking victims is selected to provide an in-depth understanding of this phenomenon. Data analysis is conducted using thematic analysis techniques, identifying key patterns in the role of KBRI in the repatriation efforts of human trafficking victims. The research also examines Indonesia's diplomatic involvement in leveraging international legal mechanisms to protect its citizens The results indicate that despite the presence of a robust legal framework and international cooperation, the implementation of protection measures still requires optimization. KBRI plays a significant role in providing legal advocacy, repatriation, and raising awareness among WNI. However, gaps in the deportation and rehabilitation processes of human trafficking victims remain major challenges. Therefore, there is a need to strengthen cross-border cooperation, enhance the capacity of diplomatic representatives, and provide continuous education to improve the protection of WNI from the threats of transnational crimes. Keywords: human trafficking, transnational crime, repatriation, Indonesian citizens (WNI)